THE NEGATIVE IMPACT OF NIAS LANGUAGE INTERFERENCE IN LEARNING INDONESIAN LANGUAGE - Evi Eunike Mendrofa (Jurnal CULTURE (Culture, Language, and Literature Review), 2020)
Most of people in the world and also Indonesian speakers are bilingualism, who use two languages; Indonesian and mother tongue. Commonly, both languages influence one another, which finally create a new phenomenon of language called interference of language. Interference of language is a form of an impact of mother tongue towards second language, which creates an error in the second language. The error occurs because the mother tongue language and the second language have different structure and different way in using the language.